2007
DOI: 10.1016/j.jen.2007.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Hygiene in the Emergency Department

Abstract: The emergency department (ED) is an essential component of the public health response plan for control of acute respiratory infectious threats. Effective respiratory hygiene in the ED is imperative to limit the spread of dangerous respiratory pathogens, including influenza, severe acute respiratory syndrome, avian influenza, and bioterrorism agents, particularly given that these agents may not be immediately identifiable. Sustaining effective respiratory control measures is especially challenging in the ED bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Because RH-CE should be implemented year round, there may be a need for periodic reminders to HCWs to ensure adequate practices. 6 Our study has clear limitations. The small sample size limited the study power, and the relatively low response rate may have introduced bias.…”
Section: Discussionmentioning
confidence: 87%
“…Because RH-CE should be implemented year round, there may be a need for periodic reminders to HCWs to ensure adequate practices. 6 Our study has clear limitations. The small sample size limited the study power, and the relatively low response rate may have introduced bias.…”
Section: Discussionmentioning
confidence: 87%
“…The emergency department is a relative high-risk department of COVID-19, and the emergency department environment in the investigated hospitals is relatively airtight. Although HCWs have adequate protections, the relatively airtight environment and high density of patients may cause aerosol transmissions in confined spaces, increasing risks of infections in the emergency department [11,12]. Further attentions need to be paid to the protection level and the environmental cleanliness of high-risk departments.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency physicians play a critical role in the early identification, treatment, and containment of potentially lethal pathogens. 1 Personal protective equipment (PPE), consisting of gowns, gloves, respiratory and eye protection, is designed to be worn by health care workers to minimize transmission of infectious agents in the workplace. 4 Hand hygiene is recognized as the best way to prevent cross-transmission of microorganisms and reduce the incidence of health care-associated infections.…”
Section: Ré Sumémentioning
confidence: 99%
“…5,6,[9][10][11][12][13][14][15][16] Potential barriers to maintaining infection control practices and using PPE in the ED include crowding, understaffing, lack of isolation facilities, lack of health care worker infection control education, high workload, high number of patient contacts, simultaneous management of multiple patients, high illness acuity, and significant time constraints. 1,17 The ED is a highrisk area for infection transmission because of high patient turnover and the frequent lack of a patient diagnosis at the time of presentation. 18 The purpose of this study was to examine the knowledge, self-reported behaviours, and barriers to compliance with infection control practices and the use of PPE in Canadian pediatric EDs.…”
Section: Ré Sumémentioning
confidence: 99%